HAMBATAN DAN DUKUNGAN DALAM MANAJEMEN DIRI PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS MLATI II - Aryuni Ekawati; Edi Sampurno; Winda Rofiyati (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
A person is said to be hypertensive if the blood pressure examination shows results >140/90 mmHg. One of the efforts to control high blood pressure is hypertension selfmanagement to avoid complications. If there are obstacles, it can affect the support for selfmanagement of hypertensive patients so that blood pressure is not well controlled. To findout the Barriers and Supports in Self-Management in Hypertensive Patients in IndonesiaWorking area Mlati II Health Center. This study uses a descriptive method with a crosssectional approach. The research location is in the Working Area of the Mlati II HealthCenter. The number of samples was 85 respondents with purposive sampling technique.The analysis used is univariate analysis in the form of frequency distribution andpercentage of each variable. The results show that management self majority good category56 people or 65.88%, Support the majority categorized enough 49 people or 57.65%, andobstaclesthe majority were categorized as 82 people or 96.47%. From this description, itcan be concluded that self-management in hypertensive patients is in good category, themajority support is sufficient, and the majority barriers are moderate. It is hoped thathealth workers, family, and peers will always provide support to be more obedient in selfmanagement and minimize obstacles.